A Case Study On Performance Management System To Support Csr Strategies - Yuliandhari, Willy Sri (2021)
The increasing concern by stakeholders regarding the management of social and environmental activities has important implications on the practice of CSR. The embedment of social and environmental issues into the corporate strategy and the deployment of performance management system promises a more effective implementation of sustainability principles, particularly CSR practices. This study aims to explore on the formulation process of CSR strategies and the utilization of PMS in implementing CSR strategies that accommodate stakeholders’ interests. The specific objectives of this study are to examine: (i) who are the key stakeholders, their requirements with regards to CSR activities and how their interests are being considered in the formulation of CSR strategies, and (ii) how the Performance Management System (PMS) is used to implement CSR strategies. A single case study method is used in this research. The company selected, PurpleCom, is a national oil and gas company wholly owned by the government, and thus its existence is intended to help the government to contribute to the development of the country’s economy, included to support the achievement of SDGs in 2030. The data is collected through semi structured interviews, document reviews, and informal conversations. This study has employed the managerial branch of stakeholder theory, Cresti’s (2009) planning and control framework, and Ferreira and Otley’s (2009) performance management system framework to analyze the data. As an SOE, PurpleCom is committed to conduct CSR activities that improve the welfare of people in the country, by accommodating the demands of its key stakeholders.